Contribution to the study of epidemiological surveillance of congenital syphilis in a hospital of the Unified Health System located in the Baixada Fluminense region, Rio de Janeiro state, Brazil - Galvão, Carolina; Borges, Wesley Caixeta; Godefroy, Philippe; Teixeira, Sergio Araújo Martins; Gerde, Eduardo Martins; Cunha, Alfredo de Almeida (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Introduction: Syphilis is a sexually transmitted disease (STD) of bacterial etiology. If it is not early diagnosed and immediately treated in pregnant women, possible repercussions can occur, such as fetal deformities, miscarriages and stillborn, or syphilitic neonate with syphilis (congenital syphilis), causing serious public health problems. Objective: To describe the prevalence of congenital syphilis in a hospital of the Unified Health System (Sistema Único de Saúde — SUS) of the Baixada Fluminense region, Rio de Janeiro, Brazil. Methods: Identified cases of congenital syphilis in the Hospital Estadual da Mãe (HMAE) from January 2013 to January 2014. Retrospective and descriptive study of data collected from medical records. Descriptive analysis with categorical variables proportions. Results: 175 cases of congenital syphilis in 6,274 births (2.7%) were analyzed. Around 80.0% of women with syphilis received prenatal care. As for the distribution of the number of sexual partners of pregnant women with syphilis who received treatment during prenatal care, only 5 of 175 records registered that their partners also received treatment, while 16 patient records contained information that the partner did not carry out the treatment, and 154 showed no information about the pregnant women partners. Conclusion: The absolute majority of cases of congenital syphilis occurred in pregnant women who had undergone prenatal care. It demonstrates that it is necessary to improve the quality of basic care in order to eliminate this severe problem of Brazilian public health.